2013
DOI: 10.1164/rccm.201203-0508oc
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10-CXCR3 Enhances the Development of Neutrophil-mediated Fulminant Lung Injury of Viral and Nonviral Origin

Abstract: CXCL10-CXCR3 signaling appears to be a critical factor for the exacerbation of the pathology of ARDS. Thus, the CXCL10-CXCR3 axis could represent a prime therapeutic target in the treatment of the acute phase of ARDS of nonviral and viral origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
249
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(264 citation statements)
references
References 43 publications
12
249
0
3
Order By: Relevance
“…A recent study demonstrated that IP-10 response enhanced the development of neutrophil-mediated fulminant lung injury of viral and non-viral origin [14]. Simi- lar to our results, they found that IP-10 was elevated in sera of patients with ARDS and the mice lacking IP-10 or CXCR3 demonstrated improved severity and survival of non-viral and viral ALI.…”
supporting
confidence: 89%
“…A recent study demonstrated that IP-10 response enhanced the development of neutrophil-mediated fulminant lung injury of viral and non-viral origin [14]. Simi- lar to our results, they found that IP-10 was elevated in sera of patients with ARDS and the mice lacking IP-10 or CXCR3 demonstrated improved severity and survival of non-viral and viral ALI.…”
supporting
confidence: 89%
“…For example, systemic IP-10 levels were significantly elevated in serum of patients with acute respiratory distress syndrome (ARDS) induced by the seasonal 2009 influenza A(H1N1) virus, compared with patients without complications [14]. Also, in a murine model, the IP-10 and CXCR3 axis enhances the development of ARDS via the recruitment of neutrophils after pH1N1 influenza virus infection [15]. Our results and these previous discoveries suggest, that in pregnancy, influenza A virus infection leads to acute and exaggerated production of IP-10 and MIP-1β by monocytes and pDCs that could contribute to ARDS and other respiratory complications, increasing the risk of influenza-associated mortality among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Released CCL2 caused an influx of monocytes to adipose tissue [33]. Recent studies showed that CD8 + T cells and neutrophils which have receptors for CXCL10 [34,35] infiltrated into adipose cells prior to an influx of monocytes [2,[36][37][38]. Thus, CXCL10 may attract CD8 + T cells and neutrophils before CCL2 causing the influx of monocytes.…”
Section: Discussionmentioning
confidence: 99%